Use of lipid-lowering drugs in restricted health access settings: Results from the Trends in Drug Utilization During COVID-19 Pandemic in Turkey (PANDUTI-TR) study - TAZEGÜL, GÖKHAN; KAŞKAL, MERT; AKICI, AHMET (My University, 2024)
Background: COVID-19 restrictions prompted changes in chronic disease management and lifestyle modifications, potentially altering cardiometabolic indicators and lipid-lowering pharmacotherapy patterns. We aimed to assess lipid-lowering drug (LLD) utilization trends during COVID-19 restrictions. Methods: We obtained nationwide outpatient drug sales and prescribing data for 01.03.2018–31.12.2022 from IQVIA™ Turkey. We evaluated average monthly LLD consumption, their costs, and quarterly prescribing levels in three periods: \"before restrictions\" (BfR, 01.03.2018–31.03.2020), \"during restrictions\" (DuR, 01.04.2020–31.03.2022), and \"after restrictions\" (AfR, 01.04.2022–31.12.2022). Drug utilization was measured via \"defined daily dose/1000 inhabitants/day\" (DID) metric. Results: LLD utilization increased from 25.4 ± 3.1 DID in BfR to 36.2 ± 6.8 DID in DuR (p < 0.001), and to 42.6 ± 5.3 DID in AfR (p < 0.001 vs. BfR). Statin consumption significantly rose from 22.0 ± 3.0 DID in BfR to 31.6 ± 6.3 DID in DuR (p < 0.001), and further to 37.6 ± 4.7 DID in AfR (p < 0.01 vs. DuR). High-intensity statin consumption elevated by 115.9% in AfR compared to baseline (p < 0.001). Prescribing of LLDs decreased from 12.5 ± 0.6 DID in BfR to 7.2 ± 1.2 DID in DuR (p < 0.001), later reached 13.6 ± 3.8 DID in AfR (p < 0.001 vs. DuR), with prescribing for ongoing users following similar trend. Expenditure on LLDs increased from €8.4 m ± 0.9 m in BfR to €11.4 m ± 2.0 m in DuR (p < 0.001) and to €12.8 m ± 1.9 m in AfR (p < 0.001 vs. BfR). Conclusions: This study revealed a surge in consumption of LLDs in Turkey following the onset of the COVID-19 pandemic. This rise might be related to practices facilitating drug access, in addition to potentially greater adherence, or the necessity for more intense pharmacotherapy due to elevated cardiovascular risk.
Keywords: Tıp; Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Biyoteknoloji; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Fizyoloji; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Biotechnology; Health Sciences; Fundamental Medical Sciences; Biochemistry; Human Physiology; Natural Sciences; Yaşam Bilimleri (LIFE); Biyoloji ve Biyokimya; Farmakoloji ve Toksikoloji; Mikrobiyoloji; FİZYOLOJİ; FARMAKOLOJİ VE ECZACILIK; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Life Sciences (LIFE); BIOLOGY & BIOCHEMISTRY; PHARMACOLOGY & TOXICOLOGY; MICROBIOLOGY; PHYSIOLOGY; PHARMACOLOGY & PHARMACY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Moleküler Tıp; Farmakoloji; Physiology; Molecular Medicine; Pharmacology; COVID-19 restrictions; Lipid-lowering drugs; Medication use; Statins